Single-position OLIF combined with percutaneous posterior fixation under O-arm navigation for the treatment of grade II lumbar spondylolisthesis: clinical and radiologic outcomes - Chen, Zhi-da; Wu, Song-song; Jiang, Yuan-jie; Liu, Hui; Huang, Zhuan-zhi; Cai, Tao-yi; Lin, Bin (Frontiers in Surgery, 2025)
Introduction and aimGrade II lumbar spondylolisthesis is frequently accompanied by segmental instability, intervertebral disc degeneration, and nerve root compression. When conservative management fails, surgery is generally warranted. Therefore, we conducted a retrospective study to evaluate the clinical and radiologic outcomes of single-position OLIF combined with percutaneous posterior fixation under O-arm navigation for the treatment of Grade II lumbar spondylolisthesis.Materials and methodsA retrospective analysis was conducted on 87 patients with Grade II lumbar spondylolisthesis who underwent single-position OLIF combined with percutaneous posterior fixation under O-arm navigation. The affected segments were as follows: 17 cases at L2, 26 cases at L3, and 44 cases at L4. Data were collected on operation duration, blood loss, hospital stay, radiological and clinical outcomes (VAS, ODI, SF-36, intervertebral disc height, slippage rate, lumbar lordosis angle, cross-sectional area, and sagittal diameter), Bridwell classification, and complications.ResultsThe mean operation duration was 118.7 ± 22.4 min, with an average blood loss of 83.6 ± 27.4 ml. All patients had regular follow up with an average duration of 29.5 ± 9.2 months. The VAS scores, ODI, and SF-36 at 3 months postoperatively and final follow-up showed significant improvement compared to preoperative scores (P < 0.05). The IDH, SR, and LLA were significantly improved at 3 days, 12 months, and at the final follow-up compared to preoperative values (All P < 0.01). Mean cross-sectional area improved significantly from 87.40 ± 29.59 mm2 preoperatively to 132.42 ± 33.53 mm2 at 12 months follow-up (P < 0.001). The mean sagittal diameter at 12 months follow-up 9.23 ± 2.87 mm showed statistically significant difference compared to preoperative measurements 5.25 ± 2.67 mm. 94.3% (82/87) of patients achieving Bridwell Grade I bone fusion. A total of 348 pedicle screws were implanted with an overall accuracy rate of approximately 98.9%. Complications were minimal, with 3 cases of psoas weakness that resolved to normal muscle strength within 2 weeks.ConclusionsIt offers significant minimal invasiveness, accuracy in screw placement, and sustained reconstruction of lumbar sagittal plane, with low complication rates and high fusion success.